METODOLOGIA PARA A CONCEPÇÃO E IMPLEMENTAÇÃO DE PROJETO DE EFICIÊNCIA ENERGÉTICA EM INSTITUIÇÕES FEDERAIS DE ENSINO SUPERIOR O CASO DA UNIVERSIDADE FEDERAL FLUMINENSE - Brasil, Clinio Freitas (2003)
The literature shows that institutional projects of efficiency energetics are common in a lot of institutions of higher education of developed countries. This fact doesn't happen in practically none of the Brazilian Federal Institutions of Higher Education - IFES -, in spite of existing in those institutions a great waste in the area of energy. The Fluminense Federal University - UFF -, in which the author participated in the conception and implementation of a project of success of that type, it is one of the rare exceptions To understand why / it because of so many existent wastes in the area of electric power use in the facilities of Brazilian IFES and how to become concept and to implement a project of energy efficiency, capable to have success in the reduction of those wastes, it was the central objective of the study. Initially, it was made a bibliographical research to identify the current apprenticeship, in the world and in Brazil, of the actions in the area of energy efficiency, in the private area and in the governmental area. With base in the experience obtained by the author in the conception and implementation of the project of energy efficiency of UFF, that he became one cases of success and in the literature analysis on projects of foreign universities, tried to identify the reasons of the success of the same ones. It was verified that the two main success factors were the adherence of them to the values and strategic objectives of the Institutions and the effective support of the high administration. With these results and, tends in view the lessons learned with the implementation of the project of energy efficiency of UFF, a methodology was elaborated for the conception and implementation of projects of energy efficiency in Brazilian Federal Institutions of Higher education